Preventing onions from frying in the heat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
In the scorching heat of east and central Burkina Faso, specialist constructed stores are being used to keep onions fresh formuch longer than ever before. Onions stored in these tin-roofed structures, which have a chimney and opening along the...